An Android-Based mHealth App for Color Vision Screening and Career Guidance: Design and Validation - Phan, Thi Yen; Dang, Vinh; Dang, Van Thanh (International Journal of Online and Biomedical Engineering (iJOE), 2025)
Color vision deficiency (CVD) affects learning outcomes, career opportunities, and daily life, but early screening in Vietnam remains limited. This study introduces an Android-based mobile health (mHealth) application for CVD screening, integrated with an artificial intelligence (AI) module for career guidance. The app was deployed with 527 high school students in Da Nang and validated against standard printed Ishihara plates. Results showed complete agreement with the traditional test, faster screening time, and positive feedback on ease of use and usefulness. The majority of students rated the CVD simulation and career guidance functions as valuable. This research contributes by (1) validating a CVD mHealth tool on a large student population in real educational settings, (2) integrating AI to link health screening with career orientation, and (3) demonstrating a cost-effective, scalable digital solution that supports both school health programs and personalized career counseling. The findings emphasize the role of engineering innovations in enhancing education and health support for students.